Evaluation of ionic degradation and slot corrosion of metallic brackets by the action of different dentifrices - Gustavo Antônio Martins Brandão; Rafael Menezes Simas; Leandro Moreira de Almeida; Juliana Melo da Silva; Marcelo de Castro Meneghim; Antonio Carlos Pereira; Haroldo Amorim de Almeida; Ana Maria Martins Brandão (Dental Press Editora, 2013)
OBJECTIVE: To evaluate the in vitro ionic degradation and slot base corrosion of metallic brackets subjected to brushing with dentifrices, through analysis of chemical composition by Energy Dispersive Spectroscopy (EDS) and qualitative analysis by Scanning Electron Microscopy (SEM). METHODS: Thirty eight brackets were selected and randomly divided into four experimental groups (n = 7). Two groups (n = 5) worked as positive and negative controls. Simulated orthodontic braces were assembled using 0.019 x 0.025-in stainless steel wires and elastomeric rings. The groups were divided according to surface treatment: G1 (Máxima Proteção Anticáries®); G2 (Total 12®); G3 (Sensitive®); G4 (Branqueador®); Positive control (artificial saliva) and Negative control (no treatment). Twenty eight brushing cycles were performed and evaluations were made before (T0) and after (T1) experiment. RESULTS: The Wilcoxon test showed no difference in ionic concentrations of titanium (Ti), chromium (Cr), iron (Fe) and nickel (Ni) between groups. G2 presented significant reduction (p < 0.05) in the concentration of aluminium ion (Al). Groups G3 and G4 presented significant increase (p < 0.05) in the concentration of aluminium ion. The SEM analysis showed increased characteristics indicative of corrosion on groups G2, G3 and G4. CONCLUSION: The EDS analysis revealed that control groups and G1 did not suffer alterations on the chemical composition. G2 presented degradation in the amount of Al ion. G3 and G4 suffered increase in the concentration of Al. The immersion in artificial saliva and the dentifrice Máxima Proteção Anticáries® did not alter the surface polishing. The dentifrices Total 12®, Sensitive® and Branqueador® altered the surface polishing. OBJETIVO: avaliar in vitro a degradação iônica e corrosão do fundo do slot de braquetes metálicos submetidos à escovação com dentifrícios, realizando análises da composição química por Espectroscopia de Energia Dispersiva (EDS) e qualitativa por Microscopia Eletrônica de Varredura (MEV). MÉTODOS: foram selecionados 38 braquetes divididos aleatoriamente em quatro grupos experimentais (n = 7). Dois grupos (n = 5) funcionaram como controles positivo e negativo. Aparelhos ortodônticos simulados foram confeccionados com fios de aço inoxidável 0,019" x 0,025" e anéis elastoméricos. Os grupos foram divididos de acordo com o tratamento de superfície: G1 (Máxima Proteção Anticáries®); G2 (Total 12®); G3 (Sensitive®); G4 (Branqueador®); Controle Positivo (saliva artificial) e Controle Negativo (sem tratamento). Foram realizados 28 ciclos de escovação e avaliações antes (T0) e após (T1) o experimento. RESULTADOS: o teste de Wilcoxon indicou não existir diferença nas concentrações iônicas de titânio (Ti), cromo (Cr), ferro (Fe) e níquel (Ni) entre os grupos. O grupo G2 apresentou redução significativa (p < 0,05) na concentração do íon alumínio (Al) e os grupos G3 e G4 apresentaram aumento significativo (p < 0,05) nas concentrações do íon alumínio. A análise em MEV mostrou aumento nas características indicativas de corrosão dos grupos G2, G3 e G4. CONCLUSÃO: a análise por EDS revelou que os grupos controle e G1 não sofreram alterações na composição química. O grupo G2 apresentou degradação na quantidade de íons Al, e G3 e G4 sofreram aumento na concentração de Al. A imersão em saliva artificial e o dentifrício Máxima Proteção Anticáries® não alteraram o polimento de superfície. Os dentifrícios Total 12®, Sensitive® e Branqueador® alteraram o polimento de superfície.